Occurrence of bisphenol A, estrone, 17b-estradiol and 17a-ethinylestradiol in Portuguese rivers - Rocha, Sónia (2014)
This study focused on the occurrence of several EDCs including bisphenol A, estrone (E1), the 17b-estradiol (E2) and 17a- thinylestradiol (EE2) in fourteen rivers of Portugal. Samples analysis revealed a widespread contamination of BPA especially in Ave, Cávado, Douro, Ferro, Sousa and Vizela Rivers. Achieving 98.4 ng/L for the highest concentration. The estrogens achieved above the method quantification limit (MQL) were E1 in Águeda River and E2 in Ave, Lima and Tâmega Rivers. The maximum concentration detected for E1 was 26.9 ng/L. EE2 was detected only below MQL.